Multiomics provides insights into dynamic changes of aromatic profile during flue-curing process in tobacco (Nicotiana tabacum L.) leaves - Ruiqi Wang; Binghui Zhang; Gang Gu; Jianfeng Lin; Wenwei Zhang; Dongwang He; Fei Wang; Liao Jin; Xiaofang Xie (BMC Plant Biology)
Abstract Tobacco (Nicotiana tabacum L.) is a globally crop due to its distinctive flavor and economic value. In this study, we systematically analyzed the dynamic changes in volatile substances, broad-spectrum metabolites, enzymes, and biochemical compounds in tobacco leaves during flue-curing process. Combining metabolomics with enzyme activity and biochemical analysis, we identified that 43℃ is a critical period for enzyme activity and metabolite transitions, while 45 ℃ requires stringent moisture control. During the T3 stages, phenolic acids, amino acids, and derivatives were notably enriched, with increases of 19.58-fold, 18.59-fold, and 17.33-fold in lmmn001643, MWS20633g, and Lmhn004756, respectively. These compounds may serve as candidate biomarkers for non-volatile compounds. Aroma dynamics primarily contributed to the green and sweet flavor of flue-cured tobacco leaves, and the key aroma components included D114, KMW1317, and KMW0466. Differential volatile and non-volatile metabolites were enriched in four pathways, including monoterpenoid biosynthesis, tyrosine metabolism, phenylalanine metabolism, and phenylpropanoid biosynthesis. These pathways are closely related to phenylalanine ammonia-lyase and the synthesis of chlorogenic acid and rutin, which influence the aroma quality, aroma intensity, irritation, and volatility of tobacco. Additionally, the contents of caffeic acid, ferulic acid, sinapic acid, and PAL activity in phenylpropanoid biosynthesis pathway, increased with the rising temperature, accelerating reactions with alcohols and leading to increase lignin formation. This study enhances our understanding of the dynamic changes in the aroma and metabolic substances of Cuibi 1(CB-1) at the critical stages of the curing process and offers valuable insights for process improvement.